Analisis Perilaku Konsumen Asuransi di Medan Sumatera Utara - Audina Rizka Zahra; Nuri Aslami (LPPM IAI Nasional Laa Roiba Bogor, 2021)
This research focuses on insurance consumer behavior, the factors that motivate insurance consumer behavior, insurance consumer behavior models, insurance consumer behavior models, insurance perceptions and insurance consumer decision-making processes. The method used in this study is a qualitative research method, namely a study that focuses on case knowledge through revealing accepted facts through interview and observation data. The results of the study obtained are to understand consumers, understand the consumption process, and improve one's personal ability to become an effective consumer. Understanding consumers and how they are consumed provides various uses, namely: helping managers to make decisions, providing researchers with a theoretical basis for researching consumers, helping legislatures and governments to legislate and make laws, and helping consumers to make better decisions. Then about consumers can help us to be able to master about the psychological, sociological, and economic factors that influence human behavior. Keywords: Behavior, Consumer, Insurance